Spectroscopic Analysis of a Theropod Dinosaur (Reptilia, Archosauria) from the Ipubi Formation, Araripe Basin, Northeastern Brazil - João Hermínio da Silva; Francisco Eduardo de Sousa Filho; Antônio Álamo Feitosa Saraiva; Nádia Amanda Andrade; Bartolomeu Cruz Viana; Juliana Manso Sayão; Bruno Tavares de Oliveira Abagaro; Paulo de Tarso Cavalcante Freire; Gilberto Dantas Saraiva (Journal of Spectroscopy)
The Araripe Sedimentary Basin is known by the excellence of its fossils, regarding the preservation, diversity, and quantity. Here, we present a spectroscopic analysis using several experimental techniques (X-ray energy dispersion spectroscopy, Fourier-transform infrared spectroscopy) as well as X-ray diffraction and thermogravimetric analysis applied in small fragments of bones from the posterior members of a theropod dinosaur. The results agree regarding the different composition of the stone matrix and the fossilized bone, indicating a partial substitution of the material by elements present in the depositional environment. However, differently from what is believed to occur, there is evidence that pyritization is not the only mechanism of fossilization for a specimen of Ipubi formation, but calcification, additionally, plays an important role in the fossil production of this Formation.